Pengaruh Brand Personality, Brand Love dan Brand Image Terhadap Brand Advocacy - Rahmawati, Oktaviya; Riyanto, Kuwat (Forum Kerjasama Pendidikan Tinggi, 2023)
This study aims to find out how brand personality, brand love and brand image influence brand advocacy (a case study on wardah cosmetics reviewers in the female daily forum). By using a quantitative method, data from this study were collected from consumers or users of some think skincare products. The sampling technique used a non-probability sampling technique with purposive sampling category, namely 108 respondents. The analytical method used in this study is data/instrument quality testing, data quality testing and hypothesis testing with the help of smartPLS 3.0 software. The results of this study indicate that there are only 2 independent variables namely brand love, brand image which have a positive and significant effect on brand advocacy. The results of testing the structural model evaluation are the R-Square value of 0.843 or 84.3% of the brand advocacy variable which is influenced by brand personality, brand love and brand image variables. While the remaining 16.7% is influenced by other variables not used in this study.